ESTIMATION OF BODY FAT USING ARM-TO-LEG AND LEG-TO-LEG BIOELETRIC IMPEDANCE ANALYSIS (Fiep Bulletin - online, 2015)
The purpose of the study was to compare estimative of percent fat in adults using arm-to-leg and leg-to-leg bioelectrical impedance analysis (BIA). Subjects were 50 adults (27 females and 23 males), with ages between 18 and 25 years. Arm-to-leg bioelectric impedance was measured using the Biodynamics 320E and leg-to-leg bioelectric impedance was measured using the Tanita TBF-305. The results indicate a strong correlations between body fat estimate by these two devices (r=0,82 for females and r=0,61 for males). However, there was a clear difference in the absolute values due to the fact that the devices measure different segments of the body. Using the Bland-Altman comparison method, a large intraindividual difference was observed in the fat percentages by the two devices, independent of adiposity level.
Keywords: Body composition; Body fat; Bioelectric Impedance